2014
DOI: 10.1053/j.ajkd.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning for Adults With CKD: A Systematic Integrative Review

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 87 publications
3
106
0
1
Order By: Relevance
“…Given the extent of comorbidity, matching patients' goals of care with the care provided throughout their disease course is of particular importance for dialysis patients. Engaging patients and families in iterative discussions about advance care planning (ACP) across the course of their illness can help increase the likelihood that patients' care goals are met (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the extent of comorbidity, matching patients' goals of care with the care provided throughout their disease course is of particular importance for dialysis patients. Engaging patients and families in iterative discussions about advance care planning (ACP) across the course of their illness can help increase the likelihood that patients' care goals are met (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Many dialysis patients and their families wish to discuss ACP with their health care providers, and such discussions are associated with positive patient outcomes (7). However, despite the existence of tools to foster such discussions (8), ACP for dialysis patients remains suboptimal (7,9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, more involvement of other important health-care providers, nurses, and social workers in shared clinical decision process along with multiple conversations with the family members, would facilitate incorporation of conservative CKD care, and educate the patients’ family regarding the best appropriate medical care for their sick family member [11,34]. Under adequate palliative care and provision of CKD care other than dialysis, most uremic symptoms can be controlled to an acceptable level and dialysis treatment might need to be provided only in rare occasions of pulmonary edema [35]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review 21 found some evidence that ACP led to increased well-being and reduced anxiety amongst patients and families. However, most studies were descriptive, and intervention studies measured a limited set of outcomes.…”
Section: Background and Rationalementioning
confidence: 99%